Hong Kong in the shadow of China living with the Leviathan - Bush, Richard C. 1947- (Brookings Institution Press, 2016)
"Hong Kong in the Shadow of China explores the recent Hong Kong turmoil, where the Chinese government insisted on gradual movement toward full democracy and protesters occupied major thoroughfares to insist on full democracy now. Fueling this struggle is deep public resentment over growing inequality and how the political system-established by China and dominated by the local business community-reinforces the divide been those who have a lot and those who have little., Richard Bush, Director of The Brookings Institution's Center on East Asia Policy Studies, considers what Hong Kong and China must do to ensure both economic competitiveness and good governance, and the implications of Hong Kong developments for United States policy"...
Keywords: POLITICAL SCIENCE / Political Ideologies / Communism & Socialism; POLITICAL SCIENCE / Political Process / Elections; Demokratisierung; Politik; Democratization -- China -- Hong Kong; Business and politics -- China -- Hong Kong; Political participation -- China -- Hong Kong; Political culture -- China -- Hong Kong; Politisches System; Innenpolitik; Hong Kong (China) -- Politics and government -- 1997-; China; Hongkong